PENGARUH LINGKUNGAN MADRASAH TERHADAP PEMBENTUKAN MORALITAS SISWA KELAS XI DI MA MUALIMIN NW ANJANI - Moh. Aldi Kurniawan Efendi (As-Sulthan Journal of Education, 2026)
Although the madrasah environment should be a place for internalizing moral values, practice shows that student behavior differs from educational goals. The influence of the madrasah environment on student morality is the subject of this study. A correlational quantitative method was used. Saturated sampling was used for the study population, which consisted of all grade XI students. Questionnaires, observations, and documentation tools were used to collect data. The validity and reliability of the questionnaire instruments were tested. Descriptive statistics, correlation tests, and simple regression were used to analyze the data with a significance level of 5%. The results of this study are that there is a significant influence on the influence of the madrasah environment on the formation of morality of grade XI students of MA NW Anjani. This can be seen based on the significance value of 0.000> 0.05 and the calculated t value of 35.145 and the t table of 3.39624. Based on the results of the analysis and data processing, it can be concluded that Ha is accepted, Ho is rejected. The results of the study indicate that the physical, social, and religious aspects of the madrasah contribute to students' attitudes, ethics, and moral behavior. To support sustainable and measurable character education in institutions, this study recommends that madrasa environments become more religious and consistent.